Functional characterization of novel alpha-helical rod domain desmin (DES) pathogenic variants associated with dilated cardiomyopathy, atrioventricular block and a risk for sudden cardiac death. (15th April 2021) - Fischer, Björn; Dittmann, Sven; Brodehl, Andreas; Unger, Andreas; Stallmeyer, Birgit; Paul, Matthias; Seebohm, Guiscard; Kayser, Anne; Peischard, Stefan; Linke, Wolfgang A.; Milting, Hendrik; Schulze-Bahr, Eric
Abstract: Background: Desmin is the major intermediate filament (IF) protein in human heart and skeletal muscle. So-called 'desminopathies' are disorders due to pathogenic variants in the DES gene and are associated with skeletal myopathies and/or various types of cardiomyopathies. So far, only a limited number of DES pathogenic variants have been identified and functionally characterized. Methods and results: Using a Sanger- and next generation sequencing (NGS) approach in patients with various types of cardiomyopathies, we identified two novel, non-synonymous missense DES variants: p.(Ile402Thr) and p.(Glu410Lys). Mutation carriers developed dilated (DCM) or arrhythmogenic cardiomyopathy (ACM), and cardiac conduction disease, leading to spare out the exercise-induced polymorphic ventricular tachycardia; we moved this variant to data in brief. To investigate the functional impact of these four DES variants, transfection experiments using SW-13 and H9c2 cells with native and mutant desmin were performed and filament assembly was analyzed by confocal microscopy. The DES _p.(Ile402Thr) and DES _p.(Glu410Lys) cells showed filament assembly defects forming cytoplasmic desmin aggregates. Furthermore, immunohistochemical and ultrastructural analysis of myocardial tissue from mutation carriers with the DES _p.(Glu410Lys) pathogenic variant supported the in vitro results. Conclusions: Our in vitro results supported the classification of DES_ p.(Ile402Thr) and DES_ p.(Glu410Lys) as novel pathogenic variants and demonstrated that the cardiac phenotypes associated with DES variants are diverse and cell culture experiments improve in silico analysis and genetic counseling because the pathogenicity of a variant can be clarified. Highlights: We identified two new DES variants. They can be classified as new pathogenic mutations Functional data and ex-vivo analysis show desmin aggregate formation.